2018
DOI: 10.22159/ijap.2018v10i6.28726
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Edible Oil Nanoemulsions for Enhanced Stability and Oral Delivery of Curcumin

Abstract: Objective: This work aims to improve the oral bioavailability and long-term aqueous stability of curcumin using various edible oil nanoemulsions (NEs).Methods: NEs were optimized using the water titration method. Curcumin was loaded into optimized emulsions, and the physicochemical characteristics were determined. Long-term stability of curcumin in the edible oil NEs was analyzed by determining the droplet size, PDI and curcumin concentrations over 4 mo. Release of curcumin from the NEs was determined using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Nanoemulsion are one of the dosage form that develop not only for oral route [25,26], topical usage [27] but also populer for parenteral usage like propofol nanoemulsion. Propofol is one of the anesthetic drug that common usage in the hospital but the pain problem make this drug become not comfortable to use.…”
Section: Resultsmentioning
confidence: 99%
“…Nanoemulsion are one of the dosage form that develop not only for oral route [25,26], topical usage [27] but also populer for parenteral usage like propofol nanoemulsion. Propofol is one of the anesthetic drug that common usage in the hospital but the pain problem make this drug become not comfortable to use.…”
Section: Resultsmentioning
confidence: 99%
“…NE can be formulated in three types: (i) oil-in-water nanoemulsion wherein oil is dispersed in the continuous aqueous phase, (ii) water-in-oil nanoemulsion in which water droplets are dispersed in the continuous oil phase, and (iii) bi-continuous nanoemulsion where the microdomains of oil and water are inter-dispersed within the system [ 19 ]. The long-term stability, spontaneous emulsification, extended shelf-life, photostability [ 20 ], and high rate of drug-solubilization capacity makes the MEs/NEs as a potent antimicrobial agent as well as a drug delivery vehicle [ [21] , [22] , [23] , [24] ]. This review aims to highlight the past two years' research findings and patent developments in antiviral NEs, antiviral EOs repurposing, and EO's role in antiviral drug delivery and vaccine formulation with a special focus on SARS-CoV2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fact that curcumin has been developed vastly in nanoemulsion form (Esperón-Rojas et al, 2020;Franklyne et al, 2018;Kamel, 2019;Ningsih et al, 2021;Ochoa-Flores et al, 2017;Páez-Hernández et al, 2019;Shelat and Acharya, 2016;Sholihat et al, 2020;Silva et al, 2018;Teixeira et al, 2016;Yu and Huang, 2012) , study of molecules interaction in curcumin nanoemulsion system is relatively scarce. Simulation studies have been reported on the interaction of curcumin with lipid bilayer (Jalili and Saeedi, 2016;Kopeć et al, 2013) or with inorganic substance (Shi et al, 2019) .…”
Section: Introductionmentioning
confidence: 99%